Contemporary Publishing Strategies in Japan: The Role of the Literary Agent - Tamaki, Yuko (TTR)

(untitled) (Association canadienne de traductologie, 2009)
Translations are shaped by publishing strategies developed by publishers and literary agents among others. However, little research has been carried out on the activities of literary agents within a particular language culture. This paper aims to describe contemporary Japanese publishing strategies in certain book categories by focusing on the role played by the literary agent. Polysystem theory and Toury’s methodology reveal that translation usually occupies a peripheral position in contemporary Japanese culture. Information drawn from an interview with a literary agent indicates that publishers exercise a great deal of influence: from initiating a translation project to micro‑managing textual details. The results of this research, reflected in both paratextual and textual features, suggest that the peripheral position of translation in Japan largely determines how translated books are produced.